The influence of ENSO on South American precipitation: simulation and projection in CMIP5 models. (25th November 2016) - Tedeschi, Renata G.; Collins, Matthew
ABSTRACT: This paper analyses the influence of different types of El Niño‐Southern Oscillation (ENSO) events on South American precipitation under a climate change scenario. We use two sub‐selections of Coupled Model Intercomparison Project Phase 5 (CMIP5) models that have a good representation of teleconnections to the region, albeit with reduced magnitude anomalies. Comparing historical simulations and the RCP 8.5 scenario experiments, after removing the trend in the mean due climate change, the sub‐ensemble means show similar global sea surface temperature anomalies and South American precipitation anomaly patterns in the future. No robust changes in the pattern or magnitude of precipitation anomalies are found, despite significant ENSO‐related shifts in the Pacific basin, as highlighted in other studies. However, if the models are analysed individually, some show relatively strong changes in ENSO‐related precipitation anomalies for both canonical and Modoki events. We show that, in individual models, tropical teleconnection changes associated with ENSO are primarily driven by changes in the magnitude of ENSO‐related circulation but with no agreement on the sign. Increases in background moisture, which have been hypothesized to drive an intensification of ENSO‐related precipitation anomalies, are of secondary importance.